2011
DOI: 10.1007/s13139-011-0103-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential Findings of Tc-99m Sestamibi Dual-Phase Parathyroid Scintigraphy Between Benign and Malignant Parathyroid Lesions in Patients with Primary Hyperparathyroidism

Abstract: For Tc-99m MIBI dual-phase parathyroid scintigraphy, uptake grade on delayed images and washout were significantly useful diagnostic criteria for differentiating benign from malignant parathyroid lesions, along with age and parathyroid hormone serum concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
2
10
1
Order By: Relevance
“…On the other hand, the retention of 99m Tc-MIBI is associated with the efflux rate of 99m Tc-MIBI from cells. A pioneering study with a small cohort of parathyroid carcinomas showed a lower washout grade of 99m Tc-MIBI from malignant parathyroid lesions than that from benign ones (17). Our study, with relatively larger samples, further indicated a significant difference of RI between malignant and benign parathyroid lesions.…”
Section: Discussionsupporting
confidence: 54%
“…On the other hand, the retention of 99m Tc-MIBI is associated with the efflux rate of 99m Tc-MIBI from cells. A pioneering study with a small cohort of parathyroid carcinomas showed a lower washout grade of 99m Tc-MIBI from malignant parathyroid lesions than that from benign ones (17). Our study, with relatively larger samples, further indicated a significant difference of RI between malignant and benign parathyroid lesions.…”
Section: Discussionsupporting
confidence: 54%
“…Patients with a confirmed parathyroid cancer usually have a higher concentration of PTH in blood serum. This is consistent with our observations and with findings in subject literature [8,[16][17][18].…”
Section: Discussionsupporting
confidence: 94%
“…The findings were evaluated using a four-point visual scale based on the comparison of tracer accumulation in the submandibular gland and thyroid gland as opposed to the parathyroid. The high uptake of radiotracer in the delayed phase and small difference in radioactivity between early and delayed uptake were among the combinations of different factors that proved useful in determining the highest possible positive predictive value for detecting a neoplastic lesions [8].…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 15 ] However, 99m Tc-MIBI SPECT/CT has not previously been fully validated for the detection of parathyroid carcinoma, though 99m Tc-MIBI-avid lesions both in early and delayed images may indicate benign adenoma. [ 16 ] In the present study, 99m Tc-MIBI SPECT/CT showed all the primary parathyroid carcinoma lesions, but planar imaging missed the primary lesion in case 2, giving a false negative result.…”
Section: Discussioncontrasting
confidence: 47%